Mixing times for the Swapping Algorithm on the Blume‐Emery‐Griffiths model. Issue 1 (28th August 2012) - Ebbers, Mirko; Knöpfel, Holger; Löwe, Matthias; Vermet, Franck
Abstract We analyze the so called Swapping Algorithm, a parallel version of the well‐known Metropolis‐Hastings algorithm, on the mean‐field version of the Blume‐Emery‐Griffiths model in statistical mechanics. This model has two parameters and depending on their choice, the model exhibits either a first, or a second order phase transition. In agreement with a conjecture by Bhatnagar and Randall we find that the Swapping Algorithm mixes rapidly in presence of a second order phase transition, while becoming slow when the phase transition is first order. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 45, 38–77, 2014